Modeling Growth of Alicyclobacillus Acidoterrestris Dsm 3922 Type Strain Vegetative Cells in the Apple Juice With Nisin and Lysozyme - Molva, Çelenk; Baysal, Ayşe Handan; Baysal, Ayşe Handan; Molva, Çelenk (AIMS Press, 2017)
In the present study, the effect of storage temperature on A. acidoterrestris DSM 3922 cells (105 CFU/mL) was examined during growth in reconstituted apple juice (pH 3.8, degrees Brix 11.3) containing nisin (0-100 IU/mL) and lysozyme (0-100 mg/L). The growth curves were obtained at three temperatures of 27, 35 and 43 degrees C using absorbance data (OD600nm). Based on the results, the minimal inhibitory concentrations (MICs) of nisin were found as 10 IU/mL at all tested temperatures. On the other hand, increasing the temperature decreased the amount of lysozyme for growth inhibition. The MICs of lysozyme were found as 10, 2.5 and 1.25 mg/L at 27, 35 and 43 degrees C, respectively. At selected non-inhibitory doses, nisin (1.25-5 IU/mL) and lysozyme (0.3-2.5 mg/L) prolonged the lag time compared to the controls at the corresponding temperatures. In addition, there was a strong linear relationship between the lag time and lysozyme concentrations at 27 and 35 degrees C (R-2 > 0.98). The results of this study demonstrated that both nisin and lysozyme could be used to inhibit the growth of A. acidoterrestris cells in the apple juice. The results also indicated that the growth parameters were variable depending on the storage temperature and the type of the antimicrobial agent used in the apple juice.
Keywords: Alicyclobacillus acidoterrestris; Apple juice; Natural antimicrobials; Modeling